Effect of storage on the physiological quality of Prosopis laevigata (H. & B.) Johnst - Muñoz-Gutiérrez, Liliana; Ríos-Saucedo, Julio César; García-García, Dora Alicia; Hernández- Pérez, César Alejandro (Ecosistemas y Recursos Agropecuarios, 2022)
Germination and vigor of mesquite (Prosopis laevigata) seeds were evaluated as a function of storage conditions. Seeds stored for 10 years, kept in glass jars at room temperature, were used. Through accelerated aging tests, vigor was determined using saturated solutions of salt, potassium chloride (KCl), lithium chloride (LiCl) and potassium bromide (KBr); and storage times (6, 12 and 24 hours). The results indicate that the seeds treated with LiCl have higher values in percentage of gemination (60%) and germination speed index (0.83) compared to the other salts and the control. However, considering the factors involved in seed germination, vigor is affected by storage conditions and vigor changes over time.